Biomedical HIV prevention research and epidemic control in Thailand: Two sides of the same coin - Frits Van Griensven (2018)
For a country with a moderate adult HIV prevalence of just over 1% in 2012, Thailand is widely perceived as having made some extraordinary contributions to the global management of the HIV/AIDS pandemic. It has been promoted as a model of effective HIV control and applauded for its leadership in providing access to antiretroviral treatment. Thailand has also received international recognition for its contribution to biomedical HIV prevention research, which is generally perceived as exceptional. In this paper, Thailand's global role model function as an example of effective HIV/AIDS control and high-quality biomedical HIV prevention research is re-evaluated against the background of currently available data and more recent insights. The results indicate that Thailand's initial response in raising the level of the political significance of HIV/AIDS was indeed extraordinary, which probably prevented a much larger epidemic from occurring. However, this response transpired in unusual extraconstitutional circumstances and its effectiveness declined once the country returned to political normalcy. Available data confirm the country's more than exceptional contribution to biomedical HIV prevention research. Thailand has made a huge contribution to the global management and control of the HIV/AIDS pandemic. © 2014 CSIRO.